2012
DOI: 10.1002/jmr.2159
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐integrase abzymes from the sera of HIV‐infected patients specifically hydrolyze integrase but nonspecifically cleave short oligopeptides

Abstract: In contrast to canonical proteases, total immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies (Abs) from HIV‐infected patients hydrolyze effectively only HIV integrase (IN), reverse transcriptase (RT), human casein, and serum albumin. Anti‐IN IgG and IgM isolated by chromatography on IN‐Sepharose hydrolyze specifically only IN but not many other tested proteins. Total Abs from HIV‐infected patients hydrolyze not only globular proteins but also different specific and nonspecific tri‐, tetra‐, and 20‐ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 44 publications
(151 reference statements)
3
42
0
Order By: Relevance
“…The relative rate of the MCA formation was approximately 4-5- (sh-OP2) and 20-25-fold (sh-OX3) higher in the presence of ms-IgG mix than that for sle-IgG mix . Similar situation was observed for longer nonspecific 20-mer oligopeptides in-OP1 and in-OP2 (Fig 1B) corresponding to viral integrase, that, as revealed by a MALDI analysis, contain several sites of IN cleavage in the case of anti-IN IgGs from HIV-infected patients [33], [34]. Nonspecific in-OP1 and in-OP2 oligopeptides corresponding to HIV integrase were slightly hydrolyzed nonspecifically after 24 of the incubation, but there was no detectable difference in the fluorescence intensities of the spots after the incubation of these OPs without (lanes 2) and with sle-IgG mix (lanes 3) (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The relative rate of the MCA formation was approximately 4-5- (sh-OP2) and 20-25-fold (sh-OX3) higher in the presence of ms-IgG mix than that for sle-IgG mix . Similar situation was observed for longer nonspecific 20-mer oligopeptides in-OP1 and in-OP2 (Fig 1B) corresponding to viral integrase, that, as revealed by a MALDI analysis, contain several sites of IN cleavage in the case of anti-IN IgGs from HIV-infected patients [33], [34]. Nonspecific in-OP1 and in-OP2 oligopeptides corresponding to HIV integrase were slightly hydrolyzed nonspecifically after 24 of the incubation, but there was no detectable difference in the fluorescence intensities of the spots after the incubation of these OPs without (lanes 2) and with sle-IgG mix (lanes 3) (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Polyclonal IgG preparations from patients with rheumatoid arthritis also displayed Pro-Phe-Arg-MCA-hydrolyzing activity [32]. Anti-integrase IgGs and IgMs from HIV-infected patients hydrolyze not only globular HIV-1 integrase but also different specific and nonspecific tri- and tetraoligopeptides [33], [34]. Therefore, first we have analyzed the efficiency of hydrolysis of nonspecific tri- and tetrapeptides using sle-IgG mix and ms-IgG mix purified by affinity chromatography on MBP-Sepharose.…”
Section: Resultsmentioning
confidence: 99%
“…Polyclonal IgG preparations from patients with rheumatoid arthritis also displayed Pro-PheArg-MCA-hydrolyzing activity [32]. Anti-integrase IgGs and IgMs from HIV-infected patients hydrolyze not only globular HIV-1 integrase but also different specific and nonspecific tri-and tetraoligopeptides [33,34]. Therefore, first we have analyzed the efficiency of hydrolysis of nonspecific tri-and tetrapeptides using sle-IgG mix and ms-IgG mix purified by affinity chromatography on MBP-Sepharose.…”
Section: Ab-dependent Hydrolysis Of Oligopeptidesmentioning
confidence: 99%
“…All sites corresponding to major and moderate products of the cleavage are shown by long and short arrows respectively, while to minor ones by diamonds (panels C and F). doi:10.1371/journal.pone.0051600.g006 KIIGQVRDQAE (in-OP2) [33,34]. All mentioned OPs contained fluorescent residue 6-O-(Carboxymethyl)fluorescein ethyl ester (X) on its N-terminus.…”
Section: Ab Proteolytic Activity Assaymentioning
confidence: 99%
“…Polyclonal antibody studies indicated that the average catalytic activity of IgMs far exceeds that of IgGs (15,19,35). IgGs develop from IgMs by a switch of C-domain gene usage, usually accompanied by immunogen-driven adaptive accumulation of V-domain mutations.…”
Section: Discussionmentioning
confidence: 99%